Exciton localization in polar and semipolar (112̅2) In0.2Ga0.8N/GaN multiple quantum wells. (30th June 2016) - Dinh, Duc V; Presa, Silvino; Maaskant, Pleun P; Corbett, Brian; Parbrook, Peter J
Abstract: The exciton localization (ELZ) in polar (0001) and semipolar (112̅2) In 0.2 Ga 0.8 N multiple-quantum-well (MQW) structures has been studied by excitation power density and temperature dependent photoluminescence. The ELZ in the (112̅2) MQW was found to be much stronger (ELZ degree σ E ∼ 40 –70 meV) compared to the (0001) MQW ( σ E ∼ 5−11 meV) that was attributed to the anisotropic growth on the (112̅2) surface. This strong ELZ was found to cause a blue-shift of the (112̅2) MQW exciton emission with rising temperature from 200 to 340 K, irrespective of excitation source used. A lower luminescence efficiency of the (112̅2) MQW was attributed to their anisotropic growth, and higher concentrations of unintentional impurities and point defects than the (0001) MQW.